The Influence of Professional Ethics, Independence, and Professional Skepticism on Audit Quality at the Regional Inspectorate Office of Palopo City - Safitri, Aisyah; Syamsuddin , Sofyan; Rusli , Andika (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2026)
This study seeks to empirically examine the influence of professional ethics, independence, and professional skepticism on audit quality within the Regional Inspectorate of Palopo City in the context of the digital era. Employing a quantitative research design, primary data were collected through structured questionnaire instruments and subsequently analyzed using multiple linear regression techniques. The empirical findings reveal that professional ethics exerts a statistically significant effect on audit quality. Similarly, independence is found to significantly enhance auditors’ capacity to maintain objectivity in the audit process. Furthermore, professional skepticism emerges as the most dominant determinant, strengthening auditors’ critical evaluation of audit evidence and their ability to identify potential misstatements or fraudulent activities. Collectively, these variables demonstrate a substantial and simultaneous influence on audit quality. The findings lend empirical support to Attribution Theory, which posits that auditors’ internal characteristics—namely ethical orientation, independence, and critical judgment—play a pivotal role in shaping professional conduct during audit engagements. Accordingly, this study underscores the imperative of reinforcing professional ethics, independence, and professional skepticism to ensure the production of more reliable, objective, and accountable audit outcomes, particularly within the public sector auditing environment.